Mindset Kewirausahaan Mahasiswa Bisnis dan Non-Bisnis - Achmad Fauzi; Iwan Setyawan (Cakrawala Management Business Journal, 2018)
Awareness of the importance of entrepreneurship and entrepreneurship is one of them manifested in the goals of higher education, as stated in Government Regulation Number 17 of 2010 which states that the goals of higher education include the development of people who are critical, creative, innovative, independent, confident and entrepreneurial. The purpose of this research is to examine whether there are differences in entrepreneurial mindset consisting of five elements, namely passion, self-leadership habits, creative habits, improvisation habits, and self-efficacy between business students and non-business students. This research was designed with a quantitative approach using two sample case analysis. The population was first semester students at the Institut Bisnis dan Informatika Kosgoro 1957. Samples were taken by stratified random sampling technique by menstruating two groups of students namely business students and non-business students. The results of the research show that there is a significant difference in the entrepreneurial mindset between business students and non-business students. This difference lies in the two elements of the entrepreneurial mindset, namely self-leadership habits and creative habits.